A novel nonsense mutation in SCAF4 associated with fliedner-zweier syndrome: a case report and review of the literature - Chen, Zhengfang; Zhao, Jing; Fan, Xiaoxuan; Xuan, Xiaoyan; Zhao, Xiaoke (Frontiers in Genetics, 2025)
IntroductionVariants in the SR-related C-terminal domain-Associated factor 4 (SCAF4) gene are linked to Fliedner-Zweier syndrome (FZS), which presents with diverse symptoms, including mild intellectual disability, seizures, behavioral abnormalities, and various skeletal and structural anomalies. However, there is a paucity of cases describing genotypes and clinical features.Case presentationWe present the case of a 4-year and seven-month-old Chinese boy displaying intellectual impairment, language development disorder, behavioral abnormalities, and distinct facial features. Whole exome sequencing (WES) identified a heterozygous nonsense mutation, c.1693C>T (p.Arg565*), located in exon 14 of the SCAF4 gene (NM_020706). Sanger sequencing confirmed paternal inheritance of this mutation. RNA sequencing from the patient demonstrated widespread transcriptional dysregulation, reinforcing the role of SCAF4 dysfunction in impaired transcription and neurodevelopmental disorders. This mutation is novel, not previously recorded in databases such as GnomAD or dbSNP, nor reported in existing literature.ConclusionWe reviewed the clinical features of the patients reported in the literature with mutations in SCAF4 gene and described the case of a Chinese patient with this mutation. This case underscores the critical need for continued exploration of genotype-phenotype correlations, enhancing our understanding of the diverse manifestations of Fliedner-Zweier syndrome and informing future diagnostic and therapeutic strategies.